Falx Meningioma, Case Report dan Review - Januarman, Januarman; Muhammad Rosyidi, Rohadi; Sutanegara, Kadek Diah Permata; Priyanto, Bambang; Hadi, Surahman; Hidayat, Teuku Ari; Abdurrosid, Lalu Muhammad Kamal (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2024)
Meningioma are tumors of the central nervous system that originate in the meninges and spinal cord. It is a benign, slow-growing neoplasm thought to originate from meningothelial cells. Meningiomas are usually oval lesions attached to the dura mater. Meningioma are most commonly located supratentorial to the calvaria or base of the meninges. Meningiomas can also be found in the tentorium, intraventricular or in the cerebellopontine position. Meningioma arise from meningothelial cap cells that are normally distributed through the arachnoid trabeculation. The greatest concentration of meningothelial cells is found in the arachnoid villi in the dural sinus, cranial nerve foramina, middle cranial fossa, and cribriform plate. Furthermore, meningiomas are commonly found over the convexity, along the falx, and at the base of the skull.